A common short-term memory retrieval rate may describe many cognitive procedures - Vergauwe, Evie; Cowan, Nelson (Frontiers in Human Neuroscience, 2014)
We examine the relationship between response speed and the number of items in short-term memory in four different paradigms and find evidence for a similar high-speed processing rate of about 25 to 30 items per second (~35 to 40 ms/item). We propose that the similarity of the processing rates across paradigms reflects the operation of a very basic covert memory process, high-speed retrieval, that is involved in both the search for information in STM and the reactivation or refreshing of information that keeps it in STM. We link this process to a specific pattern of rhythmic, repetitive neural activity in the brain (gamma oscillations). This proposal generates ideas for research and calls for an integrative approach that combines neuroscientific measures with behavioral cognitive techniques.